Service of Documents under Regulation No. 2020/1784: A View from the Lithuanian Perspective - Pranevičienė, Kristina; Limantė, Agnė (Teisė, 2025)
On 25 November 2020, Regulation No. 2020/1784 of the European Parliament and of the Council was adopted. It governs the service of judicial and extrajudicial documents in civil or commercial matters in the Member States. The Regulation entered into force on 1 July 2022 and applies in all Member States, including Denmark, when judicial and extrajudicial documents in civil and commercial matters need to be sent to another EU country. This article discusses the main innovations of Regulation No. 2020/1784, and examines the application of this regulation in Lithuania during the first three years. The article aims to contribute to the discussion on the proper service of documents in the EU and to reveal how the EU rules in this area operate in the national system.
Keywords: EU civil procedure; service of documents; Regulation No. 2020/1784; Service Regulation; service of judicial and extrajudicial documents